Building “First Expire, First Out” models to predict food losses at retail due to cold chain disruption in the last mile - Herron, Charles B.; Garner, Laura J.; Siddique, Aftab; Huang, Tung-Shi; Campbell, Jesse C.; Rao, Shashank; Morey, Amit (Frontiers in Sustainable Food Systems, 2022)
Less-than-truckload (LTL) shipping practices allow for temperature abuse (TA) in the last segment (last mile) of the food supply chain. When TA is combined with “First-In, First-Out” product rotation, food spoilage/food waste may result; therefore, data-based decision models are needed to aid retail managers. An experiment was designed using pallets (4 layers/pallet x 5 boxes/layer) of commercially produced boneless chicken breast fillet trays. Each pallet was exposed to 24 h of simulated LTL TA (cyclic 2 h at 4˚C, then 2 h at 23±2˚C). Fillet temperatures were recorded for all boxes using dataloggers. Microbiological sampling (aerobic plate counts (APC) and psychrotrophic plate counts (PSY)) was conducted before (0 h of LTL TA) and after (24 h of LTL TA) the TA experiment for select boxes and compared to control fillets (maintained at 4˚C). After TA, a shelf-life experiment was conducted by storing fillets from predetermined boxes at 4˚C until spoilage (7 log CFU/mL). Temperature and microbiological data were augmented using Monte Carlo simulations (MC) to build decision making models using two methods: (1) The risk of boxes on the pallet reaching the “danger zone” (>4˚C) was determined; and (2) The risk-of-loss (shelf-life <4 days; minimum shelf-life required to prevent food waste) was determined. Temperature results indicated that top and bottom layer boxes reached 4˚C faster than boxes comprising the middle layers while the perimeter boxes of each layer reached 4˚C faster than center boxes. Shelf-life results indicate a reduced shelf-life by 2.25 and 1.5 days for APC and PSY, respectively. The first MC method showed the average risk of boxes reaching 4˚C after 24 h of simulated LTL TA were 94.96%, 43.20%, 27.20%, and 75.12% for layers 1-4, respectively. The second MC method indicated that exposure at >4˚C for 8 h results in a risk-of-loss of 43.8%. The findings indicate that LTL TA decreases shelf-life of chicken breast fillets in a heterogenous manner according to location of boxes on the pallet. Therefore, predictive models are needed to make objective decisions so that a “First-Expire, First-Out” method can be implemented to reduce food wastes due to TA during the last mile.